(untitled) (CIVED, 2023)
The addition of Bacillus Subtilis bacteria to the mud soil at IPAM (Integrated Wastewater Treatment Plant) Perumda Tirta Manuntung Km.8 in Balikpapan City aimed to enhance its suitability as a temporary cover layer in places like landfills. Initial mud testing revealed key characteristics: Chemical Characteristics: The mud’s specific chemical composition was identified, providing a foundation for a deeper understanding of its properties. Physical Characteristics: The mud falls into the fine-grained soil category, with 63% of particles passing through a No. 200 sieve. Moisture content is high at 42.54%, primarily composed of silt (39.8%) and clay (25%). Mechanical Characteristics: Standard proctor tests yielded a maximum dry unit weight of 1.099 gr/cc and an optimum water content of 33.65%. Initial soil permeability met temporary landfill cover criteria, with a permeability value of 5.04×10-4 cm/s. Further research demonstrated that by introducing Bacillus Subtilis bacteria at varying concentrations and incubation periods, mud permeability could be altered. The highest permeability, 4.27×10-4 cm/s, was achieved with an 8% bacteria concentration and a 7-day incubation period, while the lowest permeability, 1.19×10-5 cm/s, resulted from an 8% bacteria concentration and a 28-day incubation period. These findings suggest that Bacillus Subtilis addition can modify mud permeability, making it more suitable as a temporary landfill cover. This presents a potential solution for more effective IPAM management.